Sequencing of Pax6 loci from the elephant shark reveals a family of Pax6 genes in vertebrate genomes, forged by ancient duplications and divergences. - Vydianathan Ravi; Shipra Bhatia; Philippe Gautier; Felix Loosli; Boon-Hui Tay; Alice Tay; Emma Murdoch; Pedro Coutinho; Veronica van Heyningen; Sydney Brenner; Byrappa Venkatesh; Dirk A Kleinjan (PLoS Genetics)
Pax6 is a developmental control gene essential for eye development throughout the animal kingdom. In addition, Pax6 plays key roles in other parts of the CNS, olfactory system, and pancreas. In mammals a single Pax6 gene encoding multiple isoforms delivers these pleiotropic functions. Here we provide evidence that the genomes of many other vertebrate species contain multiple Pax6 loci. We sequenced Pax6-containing BACs from the cartilaginous elephant shark (Callorhinchus milii) and found two distinct Pax6 loci. Pax6.1 is highly similar to mammalian Pax6, while Pax6.2 encodes a paired-less Pax6. Using synteny relationships, we identify homologs of this novel paired-less Pax6.2 gene in lizard and in frog, as well as in zebrafish and in other teleosts. In zebrafish two full-length Pax6 duplicates were known previously, originating from the fish-specific genome duplication (FSGD) and expressed in divergent patterns due to paralog-specific loss of cis-elements. We show that teleosts other than zebrafish also maintain duplicate full-length Pax6 loci, but differences in gene and regulatory domain structure suggest that these Pax6 paralogs originate from a more ancient duplication event and are hence renamed as Pax6.3. Sequence comparisons between mammalian and elephant shark Pax6.1 loci highlight the presence of short- and long-range conserved noncoding elements (CNEs). Functional analysis demonstrates the ancient role of long-range enhancers for Pax6 transcription. We show that the paired-less Pax6.2 ortholog in zebrafish is expressed specifically in the developing retina. Transgenic analysis of elephant shark and zebrafish Pax6.2 CNEs with homology to the mouse NRE/Pα internal promoter revealed highly specific retinal expression. Finally, morpholino depletion of zebrafish Pax6.2 resulted in a "small eye" phenotype, supporting a role in retinal development. In summary, our study reveals that the pleiotropic functions of Pax6 in vertebrates are served by a divergent family of Pax6 genes, forged by ancient duplication events and by independent, lineage-specific gene losses.